Smart Financial Management: Introducing Digital Accounting Tools for Small Businesses - Lia Nurina; Diah Nurdiana; Eko Prasetyo (PT. Global Research Collaboration, 2025)
This community service program aims to improve financial literacy and technical skills of Micro, Small, and Medium Enterprises (MSMEs) in Parit Tokaya Village, South Pontianak through accounting digitalization training. Based on initial observations, most MSMEs in this area have not used a digital financial recording system and still rely on unsystematic manual methods. The training was conducted with a participatory approach and direct practice using a simple accounting application that can be accessed via the participant's smartphone device. Evaluation of the training results was carried out through pre-test and post-test instruments, which showed a significant increase in participants' understanding and skills in managing business finances. Practice-based training methods have proven effective in increasing participant engagement and understanding. In addition, the impact of the training can be seen from changes in participant behavior who have started recording daily transactions and preparing cash flow reports periodically. Challenges in implementation remain, limited devices, internet connections, and resistance to change from older participants. To maintain the sustainability of the training results, a learning community was formed and digital ambassadors were appointed from the most active participants. This program is expected to be a replication model for other regions in an effort to strengthen the digital transformation of MSMEs. This activity not only provides individual capacity building, but also contributes to the development of a more adaptive and technology-based local economic ecosystem. Cross-sector collaboration between universities, government, and local communities is key to supporting the sustainability of this kind of community service program.